Longer mean colonoscopy withdrawal time is associated with increased adenoma detection: evidence from the Bowel Cancer Screening Programme in England - Lee, T. J. W.; Blanks, R. G.; Rees, C. J.; Wright, K. C.; Nickerson, C.; Moss, S. M.; Chilton, A.; Goddard, A. F.; Patnick, J.; McNally, R. J. Q.; Rutter, M. D. (Endoscopy, 2013)
Background and study aims: Increasing colonoscopy withdrawal time (CWT) is thought to be associated with increasing adenoma detection rate (ADR). Current English guidelines recommend a minimum CWT of 6 minutes. It is known that in the Bowel Cancer Screening Programme (BCSP) in England there is wide variation in CWT. The aim of this observational study was to examine the relationship between CWT and ADR. Patients and methods: The study examined data from 31 088 colonoscopies by 147 screening program colonoscopists. Colonoscopists were grouped in four levels of mean CWT ( < 7, 7 – 8.9, 9 – 10.9, and ≥ 11 minutes). Univariable and multivariable analysis (binary logistic and negative binomial regression) were used to explore the relationship between CWT, ADR, mean number of adenomas and number of right-sided and advanced adenomas.Results: In colonoscopists with a mean CWT < 7 minutes, the mean ADR was 42.5 % compared with 47.1 % in the ≥ 11-minute group (P < 0.001). The mean number of adenomas detected per procedure increased from 0.77 to 0.94, respectively (P < 0.001). The increase in adenoma detection was mainly of subcentimeter or proximal adenomas; there was no increase in the detection of advanced adenomas. Regression models showed an increase in ADR from 43 % to 46.5 % for mean CWT times ranging from 6 to 10 minutes.Conclusions: This study demonstrates that longer mean withdrawal times are associated with increasing adenoma detection, mainly of small or right-sided adenomas. However, beyond 10 minutes the increase in ADR is minimal. Mean withdrawal times longer than 6 minutes are not associated with increased detection of advanced adenomas. Withdrawal time remains an important quality metric of colonoscopy.